Peran Guru Pendidikan Agama Kristen Terhadap Pertumbuhan Karakter Bagi Anak Didik - Patrisius Liber; Loris Loris; Sandra R .Tapilaha (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The role of teachers in Christian-based character education is crucial in shaping individuals who are not only intellectually smart but also rich in values and ethics, especially amidst the challenges of globalization and rapid technological advancements. This research aims to develop teaching methodologies that can support Christian religious education teachers in their duties, specifically in designing and implementing an effective curriculum to help students understand and apply Christian values in daily life. The research method to be used is literature research, involving the collection of data related to the discussed theme from primary sources such as books, scientific journals, and others. The research findings indicate that Christian Religious Education teachers play a vital role in forming students' character to reflect the teachings of Lord Jesus Christ through the teaching of Christian values and by being models in behavior, attitude, and ethics. Effective character education requires support from a conducive learning environment, including the commitment of the school community, a curriculum that is integrated with values and ethics, visionary leadership from the school principal, and solid teamwork, despite challenges such as limited resources, lack of parental support, and apathetic attitudes from some parties.